Nietzsche and modern German thought - Ansell-Pearson, Keith, 1960- (Routledge, 1991)
Nietzsche is no longer a marginal figure in the study of philosophy. This collection of specially commissioned essays reflects the emergence of a serious interest amongst philosophers, sociologists and political theorists. By considering Nietzsche's ideas in the context of the modern philosophical tradition from which it emerged, his importance in contemporary thought is refined and reaffirmed. Modern German thought begins with Kant and has rarely escaped his influence. It is with respect to this Kantian heritage that this volume examines Nietzsche. These essays critically consider Nietzsche's relation to Kant and the post-Kantian tradition. In broad terms it is his relation to the domains of knowledge, ethics and aesthetics, that is through the three Kantian critiques, that Nietzsche's thought is illuminated. This allows a surprising variety of areas and questions, both about Nietzsche and about philosophy to be investigated.; The whole question of tradition is raised in assessing Nietzsche's achievement: Valuable insights are gained into neglected and relatively unknown aspects of Nietzsche's thought in relation to, for example, hermeneutics or Lange; original and challenging interpretations of central notions of modernitye merge in discussions of the self and the will; the continuing importance of Kant's Critique of Judgement is reaffirmed in its relation to Nietzsche's attempts to arrive at a new tragic post-metaphysical style of philosophy.